Analisis Supply Chain Management Keripik Keladi Pada Usaha Tunas Jaya Manokwari - Angelin, Ruth; Saptomo, Yulius Heri; Sudarwadi, Dirarini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This research aims to determine the application of taro chips supply chain management activities at Tunas Jaya Manokwari Business and to determine the flow of the taro chips supply chain at Tunas Jaya Manokwari Business.In this research, the author uses qualitative research with a case study approach. The data sources used are primary data and secondary data. Primary data is data obtained from interviews, observations and documentation at Usaha Tunas Jaya Manokwari and secondary data is data obtained from references related to research.The results of the research show that: (1) the application of supply chain management for taro chips at Usaha Tunas Jaya has been running optimally because it has built integrated relationships and good collaboration between supply chain actors from upstream to downstream. (2) The entire supply chain flow in this business is running well by exchanging information, where every agreement made never harms either party, there is a level of trust in each other so that long-term relationships can be established and all parties are well integrated. in distributing taro chips products to consumers. Keywords: supply chain management; supply chain flow; Tunas Jaya Manokwari